El espacio común producción artística en y acerca de la ciudad : 2019-2020 = The common space : artistic production in, and about, the city : 2019-2020 - Blanco, Lisa; Hidalgo, María Eugenia (Museo de Arte de Puerto Rico, 2022)
The book explores the constant transformations that the urban environment in Puerto Rico has experienced in the last ten years through an exhibition that reviews the diversity of approaches to the phenomenon of the city among contemporary artists. The constant transformations that the urban environment in Puerto Rico has experienced in the last ten years are reflected through various approaches by contemporary artists. Curated by artist and academic Vanessa Hernández Gracia, the catalogue features murals, graffiti, ephemeral interventions, performance, painting, installations, found objects, photography and video, made in the city of San Juan by artists of several generations, mostly born or resident on the island. As the curatorial text states, "Among this display of particularities, urban interventions appear, which arise in an infinite number of forms and have the capacity to transform the urban landscape from artistic expressions that reflect the socio-political and environmental concerns of artists, as well as collectives."